Analisa Dukungan Dan Hambatan Dalam Pembelajaran Rumpun Keilmuan Pendidikan Agama Islam di MTs. Unggulan Sabilillah Lamongan - Rokim, Rokim; Abdul Manan; Miftachur Rochmah (Universitas Islam Lamongan, 2024)
This research talks the support and obstacle analyis of the learning of scientific group Islamic educational studies in MTs Unggulan Sabilillah Lamongan by using the descriptive qualitative research. The purpose of this research is figuring out the analyis of the learning of Islamic studies’ progress in Madrasah Tsanawiyah Unggulan Sabilillah lamongan. Additionally, this research has been planned to be used for knowing the support and obstacle aspect of the Islamic studies component in Madrasah Tsanawiyah Unggulan Sabilillah Lamongan. The research is the support and obstacle analyis in the scientific group of Islamic studies learning which uses the interactive learning and pays attention the students’ veriety in learning and fulfills their needs based on the Madrasah Tsanawiyah’s context. The improvement of materials must be structured according to the judgement effectivity and the additional learning source development to support the outside learning class. Telling the Islamic studies by using the appropriate and relevant method according to the experiences and the needs of the students. The supporting factor for the teachers in the scientific group learning in the Islamic studies come from various sources, including teachers’ private books, other book types and the internet. Additionally, the teachers have used the variety of learning methods such as the utilize of LCD, video, and the appropriate literacy according to the materials. In contrast, the obstacle is the irrelevant curriculum, the repeated learning method, and the lack of the students’ involvement. Following that, the small number of the material sources from various Islamic studies learning books, the difficulty of finding and creating the relevant materials according to the students’ life and the lack of the learning approach’s relevance based on students’ needs